Yeast-extracted nucleotides and nucleic acids as promising feed additives for European sea bass (Dicentrarchus labrax) juveniles - Pelusio, Nicole Francesca; Parma, Luca; Volpe, Enrico; Ciulli, Sara; Errani, Francesca; Natale, Silvia; De Cesare, Alessandra; Indio, Valentina; Carcano, Paolo; Mordenti, Oliviero; Gatta, Pier Paolo; Bonaldo, Alessio (Frontiers in Marine Science, 2023)
Nowadays functional ingredients have a significant potential for improving current low fish meal (FM) aquafeed formulation in sustaining growth and enhancing animal robustness for Mediterranean aquaculture. Among them, nucleotides (NT) and nucleic acids (NA) drew attention for their application in the last two decades. NT are organic molecules involved in many life-supporting pathways, and are the building blocks of NA, which stand as genetic repositories. NT are naturally present in organic ingredients, and among them FM is known to be one of the highest NT sources. When this NT source is seriously limited, fish might be under the minimum NT requirements, especially in fast growing life stages of carnivorous species. Hence, a trial on European sea bass juveniles was carried out, testing two dietary FM levels (FM10, FM20 as 10% and 20% FM, respectively) supplemented with 500 mg kg-1 yeast-originate NT or NA dose over 80 days. Thereafter, fish were exposed to one week of sub-optimal thermal and dissolved oxygen condition (30°C and 4.0 mg/L O2) to further explore the effect of NT and NA inclusion on immune response and gut microbiome alteration. At the end of the growth period NT increased feed intake at both FM dietary levels. FM20 combined with NA and NT further improved growth performance, enhancing lipid efficiency and increased anti-inflammatory TGF-β. After sub-optimal environmental conditions both NT and NA exerted prebiotic functions on gut microbiome by promoting beneficial lactic acid bacteria such as Weissella and Leuconostoc. At the same time NT in 10% FM diet increased the abundance of Bacillus taxon. In conclusion, the combination of NT/NA included at 500 mg kg-1 was able to promote growth when included in 20% FM level, assuming higher nutritional NT requirement when combined with 10% FM. On the other hand, NT/NA added in 10% FM upregulate proinflammatory IL-1β and favor beneficial gut bacterial taxa.